Fortifikasi Kacang Gude (Cajanus cajan) pada Bagiak (Osing Etnich’s Snack) Sebagai Camilan Diet Tinggi Nutrisi - Ulfa, Rosiana; Arista, Yuvita L V; Setyawan, Bagus; Utami, Arfiati U (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Bagiak is one of the traditional cakes or snacks originating from Osing Etnich’s Snack, made from sago starch, tapioca, arrowroot starch, and flavoring. The results of a Snapchart study show that Indonesians generally choose snacks with high calories and low nutrition, which can be a severe problem. One effort that can be made to overcome this problem is fortification. Fortification of bagiak can be done by enriching the mineral, crude fiber, and protein sourced from pigeon peas (Cajanus cajan). Therefore, this study was conducted to determine the effect of adding pigeon pea flour on the nutritional content of bagiak, especially moisture content, protein, ash, crude fiber, and fat. The study used the completely randomized design method of 5 levels, including adding pigeon pea flour 0, 15, 30, 45, 60, and 75%. The test results were subjected to variance analysis and continued with DMRT. The results showed that the addition of pigeon pea flour (C. cajan) at various concentrations has a significant impact (p < 0.005) on the moisture content, protein, fat, ash, and crude fiber content of bagiak. The higher addition of pigeon pea flour was directly proportional to the increase in the nutritional content of bagiak. Adding 75% pigeon pea (G5) produced bagiak with the highest nutritional content; the protein content was 15.07%, moisture content 4.52%, ash 4.02%, crude fiber 10.96%, and fat 19.36%. The bagiak produced exceeded the quality standards set by BSN in SNI 2973:2022.